2016
DOI: 10.1111/cea.12660
|View full text |Cite
|
Sign up to set email alerts
|

Stability and predictiveness of multiple trigger and episodic viral wheeze in preschoolers

Abstract: Stable multiple-trigger and stable episodic viral wheeze are relatively uncommon. However, 1- to 3-year-olds with stable MTW are at much increased risk of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 34 publications
3
40
0
1
Order By: Relevance
“…Furthermore, we found that the prevalence of MTV—although increasing relatively as a proportion of all children with wheeze—does not change much in absolute prevalence throughout childhood, affecting between 8% and 12% of children at all ages. It has been questioned whether these phenotypes are stable over time and thus independent disorders . However, recent data from the Leicester Respiratory Cohorts and the Avon Longitudinal Study of Parents and Children cohort (ALSPAC) suggest that MTW and, to a lesser extent, EVW track throughout childhood, independent of severity, and thus seem to be separate disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the prevalence of MTV—although increasing relatively as a proportion of all children with wheeze—does not change much in absolute prevalence throughout childhood, affecting between 8% and 12% of children at all ages. It has been questioned whether these phenotypes are stable over time and thus independent disorders . However, recent data from the Leicester Respiratory Cohorts and the Avon Longitudinal Study of Parents and Children cohort (ALSPAC) suggest that MTW and, to a lesser extent, EVW track throughout childhood, independent of severity, and thus seem to be separate disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Although the pattern of episodic viral wheeze has been well described in the literature and advocated as a management tool by a European Respiratory Society Task Force, 8 recent studies have demonstrated that most preschool children quickly change from 1 phenotype to another. 47 Given these limitations, therapeutic decisions remain challenging until more studies are conducted that clearly describe the disease pattern and baseline risk of enrolled children and directly compare daily ICS, intermittent ICS, and montelukast. Our findings show significant reductions in risk of moderate to severe exacerbations with ICS, and they support initiation of ICS therapy in preschool children with symptoms of persistent asthma or those with high risk of severe exacerbations (>1 course of systemic steroids per year).…”
Section: Figurementioning
confidence: 99%
“…Although this phenotype distinction appears straightforward, a Canadian study showed considerable variation between physicians in the phenotype assessment of the same patient vignettes . In addition, considerable within‐patient phenotype switching has been reported in two prospective cohort studies in primary and hospital‐based pediatric care, with up to 80% of phenotype changing in children with recurrent wheeze over a period of 1 to 2 years . Conversely, in two large population‐based birth cohort studies, Spycher et al recently reported a tendency of wheeze phenotypes to track in children who continued to wheeze between the ages of 2 and 7 years.…”
Section: Introductionmentioning
confidence: 99%